Drop-out from the Swedish addiction compulsory care system. (April 2015) - Padyab, Mojgan; Grahn, Robert; Lundgren, Lena
Highlights: The study explores the extent of drop-out of compulsory care in Sweden. Merging data from two national register databases, 4515 clients are included. We identified drop-out of compulsory care is associated with negative outcomes. New interventions with specific focus on increasing motivation of youth are needed. Abstract: Drop-out of addiction treatment is common, however, little is known about drop-out of compulsory care in Sweden. Data from two national register databases were merged to create a database of 4515 individuals sentenced to compulsory care 2001–2009. The study examined (1) characteristics associated with having dropped out from a first compulsory care episode, (2) the relationship between drop-out and returning to compulsory care through a new court sentence, and (3) the relationship between drop-out and mortality. Methods: Multivariable logistic regression analysis was used to address Aim 1 and Cox proportional hazards regression modeling was applied to respond to Aims 2 and 3. Findings: Age and previous history of crime were significant predictors for drop-out. Clients who dropped out were 1.67 times more likely to return to compulsory care and the hazard of dying was 16% higher than for those who dropped-out. Conclusion: This study finds that 59% of clients assigned to compulsory care drop-out. Younger individuals are significantly more likely to drop-out. Those who drop out are significantly more likely to experience negative outcomes (additional sentence to compulsory care and higher risk of mortality). Interventions need to be implemented that increase motivation of youth to remain in compulsory care.